Sosialisasi Keagamaan sebagai Upaya Peningkatan Pemahaman Masyarakat Desa Tejo Kecamatan Mojoagung tentang Perawatan Jenazah - Muhamad Khoirur Roziqin; Muhammad Fodhil; Muhammad Nasrullah; Umul Khoirun Nisa; Syarifatul Chofifah; Nur Elyatul Chumaidah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Most Tejo village residents are Muslim but do not participate in many Islamic activities in their daily lives. In this case, a problem arises regarding caring for corpses because some residents still have little knowledge of corpse care, which is very important for society. One small example of caring for a corpse is praying, washing, shrouding, and burying, and this problem must be resolved through community service activities. The objectives of this service include: a) Increase the understanding of youth members of the Darul Jalal Mosque and religious organizations in Tejo village regarding the care of corpses. b) Growing a generation of teenagers who understand the care of corpses. This service activity was carried out at the Darul Jalal Mosque, Tejo Village, Mojoagung District on September 9, 2023. 23 participants attended this activity. This service activity used discussion and training methods. Data collection via questionnaire after socialization regarding participant enthusiasm. The results of community service activities showed that the level of enthusiasm among teenagers at the Darul Jalal Mosque increased by around 95.6% because after this socialization was held, many of the participants understood the material presented by the resource person and many of the participants were also active in discussion forums during the socialization